Одеські адреси скульптора Бориса Едуардса - Кудлач, В. (Краєзнавство, 2016)
Стаття присвячена Борису Едуардсу, видатному одеському скульптору європейського рівня
у період його активної виставкової діяльності як члена Товариства південноросійських художників (ТПРХ) у першій половині 1890-х рр. На основі довідкової та адресно-довідкової літератури, каталогів виставок ТПРХ, мап міста та окремих мистецтвознавчих видань досліджується місце проживання Б. В. Едуардса в Одесі в означений період. The article is devoted to Boris Edwards, a prominent Odesa sculptor of European level, during its
active exhibition activities as a member of the Association of the South Russian artists in early 1890.
Boris Edwards’ residence in Odesa during that period is studied on the base of reference books, exhibition
catalogs of the association, maps and some art history books.
Boris Edwards (1860-1924) – son of merchant, Russified British partial of Irish origin and Ukrainian
aristocrat of Maksimovic family. The article used documents from the collections of the Odesa
National Research Library, the State Archives of Odesa region, publications in scientific collections.
Edwards entered the history of Ukrainian art as a talented sculptor who has successfully worked
as a muralist and author of chamber works. Portrait genre and works of religious themes were the
priority in his work. Among the famous works of master – a group of sculptures “Christ and the Sinner”
(silver medal at the World Exhibition in Paris, 1900); busts of Louis Pasteur, “Shurka”, monuments
of Andreyevskiy E., A. Pushkin, M. Gogol, Alexander Suvorov. Among his latest sculptures – “The lady in the chair” created in Malta, where the sculptor emigrated in 1919. This work was exhibited in 1923 at the Colonial Exhibition. In 1890, the enterprising sculptor opened the Atelier of Art and Industry sculpture at Sofievska Street, 18, and four years later – a bronze foundry in the courtyard of his house in Sofievska Lane, which was the first workshop of such type in Ukraine. Статья посвящена Борису Эдуардсу, выдающемуся одесскому скульптору европейского
уровня в период его активной выставочной деятельности как члена Товарищества южнорусских художников (ТЮРХ) в первой половине 1890-х гг. На основе справочной и адресно-справочной литературы, каталогов выставок ТЮРХ, карт города и отдельных искусствоведческих
изданий исследуется место проживания Б. В. Эдуардса в Одессе в упомянутый период.